Speeding up the study of diluted dipolar systems - Mártin, Daniel Alejandro (2019)
We study the regimes of a diluted dipolar system through Monte Carlo numerical simulations in the NVT ensemble. To accelerate the dynamics, several approximations and speed-up algorithms are proposed and tested. In particular, it turns out that "cluster move Monte Carlo" algorithm speeds-up to two decades faster than the traditional Monte Carlo, depending on temperature and density. We find simple-fluid, chain-fluid, ring-fluid, gel, and antiparallel columnar regimes, which are studied and characterized through positional, orientational, and thermodynamical observables.